Development Of Smart Box Literacy Media To Improve Early Reading Skills Of Grade II Students - Fajrin, M; Trimansyah, Trimansyah; Mulyadin, Mulyadin (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to develop Smart Box Literacy–based learning media and examine its effectiveness in improving the beginning reading skills of grade II students at SDN Rato, Lambu District. The research employs a Research and Development (R&D) method using the Borg and Gall development model, which was modified into five stages: (1) preliminary study, (2) planning, (3) initial product development, (4) limited-scale trials, and (5) product revision. This study involved 18 grade II students as research subjects. The results show that the Smart Box Literacy media is valid and suitable for use in beginning reading instruction, with validation scores of 92% from media experts (very valid category) and 90% from material experts (very valid category). The effectiveness test using paired sample t-test statistical analysis indicated a significant increase in students’ average reading scores after using the media compared to before its use. Furthermore, both teachers and students gave highly positive responses to the media, noting that it was engaging, easy to use, and helpful in improving students’ reading comprehension. Therefore, Smart Box Literacy is declared effective and feasible to be used as an innovative, engaging, and relevant learning medium to enhance beginning reading skills at the elementary school level.